Note sulla Laguna di Venezia in epoca Romana - Iwona Modrzewska-Pianetti (Studies in Ancient Art and Civilization, 2013)
The author use key hydrographic, climatic and textual sources to reconstruct the changing landscape of the Venetian Lagoon, enabling us to track the alterations which have taken place here from Roman times up to the present day.